"O samba como instrumento de transformação social”: afeto, cultura e política na comunidade de samba do pagode da 27 - Musa, Nicolau Augusto (2023)
This dissertation discusses the politics made by the popular classes through peripheral cultural collectives. Specifically, the objective is to discuss what shapes and drives this political form of peripheral cultural collectives, their modes of operation and their consequences. The ethnographic research was conducted with Pagode da 27, a samba community located in Grajaú, in the southernmost part of the city of São Paulo. To obtain the data, a follow-up was made of the routine of members and situations of musical practice and social projects of Pagode da 27. In addition to observation, interviews and music analysis were conducted. From the analysis, three arguments emerge that help to understand the shaping and driving of the political practice of agents through the Samba Community: a) samba as a cultural practice and tradition is of great importance in the production of bonds between agents, in the ways they think of themselves and in the direction they give to their actions; b) shared affections between agents and their affections towards samba are a primary factor for them to build the collective and act through it; c) the meanings given by agents of what it means to be a "samba community" and the practices linked to this are central to transforming cultural and affective dimensions into political organization.